Twin Deficits and Feldstein-Horioka Puzzle in the Case Iran - Bagheri, Farzane; ., Fatemeh Daroghe Hazrati (Journal of Social and Development Sciences, 2012)
The main purpose of this study is to examine the relationship between budget deficit and current account deficit in Iran’s economy through twin deficits and Feldstein-Horioka puzzle. To achieve this goal, Engel-Granger and seemingly unrelated regressions are used during "1971-2007". The results indicate that there exists a long run equilibrium link between budget deficit and current account deficit. There is a oneâ€“way causality relationship from the budget deficit toward the current account deficit .Testing the validity of the Feldstein-Horioka puzzle indicates a low level of international capital mobility for Iran.